The Association of Trp64Arg Polymorphism in the Beta-Adrenergic Receptor With Insulin Resistance: Meta-Analysis - Wang, Hai-Dan; Zhang, Cai-Shun; Li, Man-Wen; Lin, Qian; Zhang, Qing; Liu, De-Feng; Ma, Zheng-Ye; Dong, Jing (Frontiers in Endocrinology, 2021)
Background Insulin resistance is a metabolic disorder that occurs in type 2 diabetes mellitus and obesity. Genetic factors such as β3-adrenoceptor polymorphism (Trp64Arg) may be involved in IR and insulin secretion. However, their association is controversial. Therefore, the current meta-analysis was conducted to clarify the relationship between the Trp64Arg and IR. Methods The literature search was performed in PubMed, Embase, and Web of Science using the keywords “Receptors, Adrenergic, beta-3, Receptors, Adrenergic, Insulin Resistance, Protein-Coupled Receptor Kinase 3” from 2005 to February 7, 2021. We used a random-effects model to calculate the pooled effect size. We conducted subgroup analysis and regression analysis to identify sources of heterogeneity; and Egger’s test and funnel plot were used to test publication bias. Finally, we conducted a sensitivity analysis. Results We included eight papers with 1,586 subjects. There was a positive correlation between Trp64Arg mutation and insulin level (standardized mean difference = 0.20, 95% confidence intervals: 0.00 to 0.39, I2 = 57.6%, p = 0.016). However, there was no association between Trp64Arg and the homeostasis model (HOMA-IR) assessment. Egger’s tests showed no publication bias; the sensitivity analysis showed that our results were stable. Regression analysis revealed no source of heterogeneity. Conclusion Trp64Arg may be associated with IR. European ancestry, obesity, plasma insulin level, and test status may be potential factors affecting the relationship between Trp64Arg and IR.